Acupuncture for Female Infertility: Discussion on Action Mechanism and Application. (4th July 2022) - Xu, Jing-yu; Zhao, An-lan; Xin, Ping; Geng, Jun-ze; Wang, Bao-juan; Xia, Tian
Abstract : A higher incidence of female infertility has been reported with an unexpectedly early appearance in recent years. The female infertility treatment and application of assisted reproductive technology have recently gained immense interest from scientists. Many studies have discussed the beneficial effects of acupuncture on female infertility. With advancements in science and medical technology, acupuncture-related research has increased in investigating its effectiveness in treating female infertility. This review focuses on a compilation of research in recent years on acupuncture for female infertility treatment and the exploration of the underlying mechanism. For this purpose, literature was searched using various search engines like PubMed, Web of Science, and Google Scholar. The search was refined by only focusing on recent studies on acupuncture effectiveness and mechanism in female infertility and evaluating pregnancy outcomes.